Una metodología para la planificación del transporte urbano - Darbéra, Richard (Revista EURE - Revista de Estudios Urbano Regionales, 1982)
The urban transporting planning (UTP) method, especially when applied in less developed countries (LDC’s), is no a scientific proccess that will automatically lead to the optimum solution. Models, elaborated in developed countries, do not always address the relevant categories in LDC’s. The calibration of these models have data requirements far beyond what is avalaible from the local statistical series collected by LDC’s institutions and beyond what could be obtained by surveys carried out within reasonable budget constraints. The projection of socio-economic variables and land-use patterns is very questionable when population growth is rapid and accentuated by rural pushed migration, when economic policy is subject to drastic modifications, and when local governments have little effective controls over urban land use development. Thus the UTP method appears to be a sequence of two types of modules: rigid ones, in wich huge amounts of data with illusory precision are generated, and flexible ones where some critical parameters are generated through more subjective processes. The rigid phases give the methodology its apparent image of scientific accuracy. The other steps are the ones where the past experience of the consultant is critical, and his apparent freedom and "scientific neutrality" is constrained by internal and external pressures exercized by personalities, institutions or organized groups (local and international). The internal pressures aim at modifying the study’s output: the transport policy to be implemented (or not). The external ones aim at objectives independent from the transport policy but in fields in which the UTP process it self interferes. The confidency interval of the output of these studies is very wide. Therefore, the evaluation of alternative plans and the choice of the "best" policy seems impossible. However, these studies are performed, and the projects are often implemented. This suggests that to be understood, the U.T. problem and consultant intervention must be analyzed in other terms. When a set of urban contradictions, defined in terms of social economic and political relations, sesms to call for a U.T. project to resolve them, the UTP consultant is contracted. His task is to internalize all the constraints, formulate the transportation investment that would be better accepted (the "solution" may already be well known), and specify it quantitatively to insure coherence with existing U.T. infraestructures and to comply to the accepted rules of economic evaluation. This approach of the UTP process in LDC’s helps to explain several case figures: inconclusive succession of studies like in Calcutta or Cairo, reorientation of policies prior to studies like in Rio, conflicting studies and their resolution like in Teheran, or major U.T. investment without prior study like in Mexico.